Different Doses of Fingolimod in Relapsing-Remitting Multiple Sclerosis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wu, Xin; Xue, Tao; Wang, Zilan; Chen, Zhouqing; Zhang, Xuwei; Zhang, Wei; Wang, Zhong (Frontiers in Pharmacology, 2021)
Background: The efficacy and safety of fingolimod for relapsing-remitting multiple sclerosis (RRMS) had been well verified in several large randomized controlled trials (RCTs) during the past decade. However, there are fewer systematic comparisons of different doses of fingolimod and which is the best fingolimod dose for RRMS patients still remain to be solved. Objective: The objective of this systematic review was to evaluate the efficacy and safety of the four existing doses of fingolimod in the treatment of RRMS. Methods: MEDLINE, EMBASE, Cochrane Library and clinicaltrials.gov were searched for RCTs which were performed to evaluate different doses of fingolimod and the corresponding control (placebo or DMTs) up to October 2020. Review Manager 5.3 software was used to assess the data. The risk ratio (RR) and mean difference (MD) was analyzed and calculated with a random effect model. Results: We pooled 7184 patients from 11 RCTs. Fingolimod 0.5 mg/d was superior to control group in all eight efficacy outcomes including annualized relapse rate (ARR) (MD −0.22, 95%CI −0.29 to −0.14, P<0.00001 ) but surprisingly showed a higher risk of basal-cell carcinoma (RR 4.40, 95%CI 1.58 to 12.24, P=0.004). Although 1.25 mg/d is more than twice the dose of 0.5 mg/d, the effect size was almost similar between them. Dose of 5 mg/d obtained an unsatisfactory efficacy while showing a greater risk of adverse events than other three doses (RR 1.17, 95%CI 1.05 to 1.30, P=0.003). Additionally, fingolimod 0.25 mg/d not only showed a better performance in delaying the disease progress of MRI, but also achieved a certain degree of patient treatment satisfaction. Conclusion: At present, 0.5 mg/d seems to be the optimal dose of fingolimod for RRMS patients but trials of a lower dose are still of great clinical significance and should be paid more attentions.